2022
DOI: 10.1111/gove.12723
|View full text |Cite
|
Sign up to set email alerts
|

Government responsiveness and citizen satisfaction: Evidence from environmental governance

Abstract: Prior research has overlooked the dynamics between government responsiveness and citizen satisfaction. This article addresses this gap by examining (1) how styles of government responses affect citizen satisfaction differently and (2) how external events moderate the effects of government responsiveness on citizens. Drawing upon 79,360 environmental demands sent to local leaders in China and 100,905 Chinese citizens' environmental assessments collected from 2013 to 18, this study finds that actional and explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Within the realm of structures and processes, public employees’ values, ethics, and motives play a pivotal role in shaping organizational outcomes, ultimately leading to heightened citizen satisfaction. Our review reveals that values such as morality, responsiveness, ethics, neutrality, and competitor orientation are positively associated with citizen satisfaction (Ariely, 2013; Nie & Wang, 2022; Walker et al, 2011; Wong et al, 2011), while organizational politics and corruption exhibit a negative correlation with citizen satisfaction (Park & Blenkinsopp, 2011; Vigoda-Gadot, 2007).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Within the realm of structures and processes, public employees’ values, ethics, and motives play a pivotal role in shaping organizational outcomes, ultimately leading to heightened citizen satisfaction. Our review reveals that values such as morality, responsiveness, ethics, neutrality, and competitor orientation are positively associated with citizen satisfaction (Ariely, 2013; Nie & Wang, 2022; Walker et al, 2011; Wong et al, 2011), while organizational politics and corruption exhibit a negative correlation with citizen satisfaction (Park & Blenkinsopp, 2011; Vigoda-Gadot, 2007).…”
Section: Resultsmentioning
confidence: 92%
“…In our review, 20 empirical studies (16.4%) have developed or uncovered some complex causal pathways by including moderators in their analyses (e.g., Baekgaard & Serritzlew, 2020; Dahlström et al, 2018; Ho & Cho, 2017; Nie & Wang, 2022; Song et al, 2021; Song & Meier, 2018). Table 6 and Appendix 4 detail a total of 28 moderators that possess the potential to either fortify or attenuate the hypothesized relationships between antecedent variables (here, a set of abovementioned antecedents) and citizen satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, Pulido-Fern andez and Pulido-Fern andez (2018), Bono and Clav e (2020) and Thayele et al (2023) studies have been modified to incorporate the tourism governance. Previous research has stated that governance affects consumer satisfaction (Nie and Wang, 2022;Gregg and Van Ryzin, 2007). In the context of tourism, governance is considered important in providing satisfaction to tourists.…”
Section: Tourism Governancementioning
confidence: 99%
“…For instance, Liu et al (2015) found that campaign‐style enforcement contributed to the significant reduction in SO 2 and smoke dust emissions in the coal‐fired power sector from 2006 to 2010 (the 11th Five ‐Year Plan period). Jia and Chen (2019) found that the program initiated by the central government for inspecting the environmental enforcing behaviors of local governments, which was not a routine part of the environmental governance system, helps improve air quality in the past few years; others found such a program helps enhance firms' environmental information disclosure (Pan & Yao, 2021) and citizen satisfaction (Nie & Wang, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%